Basketball - Wright, John D., 1938- 4 0 16; 5 (Broomall, PA : Mason Crest Publishers, 2004)
Introduces the sport of basketball and provides information on how to prevent and treat the most common basketball injuries.
History -- The mental game -- Fitness to avoid injury -- Injuries and treatment -- Careers in basketball.
Includes bibliographical references (p. 62) and index.
Keywords: 2 -- 0; 6; Basketball;Basketball injuries;Basketball.;Sports injuries. -- 20 -- Juvenile literature.;Juvenile literature; 20; 2